The Effectiveness of Preoperative Preparation for Improving Perioperative Outcomes in Children and Caregivers. Issue 3 (May 2019) - Lin, Chia-Jung; Liu, Hsin-Ping; Wang, Pei-Ya; Yu, Mei-Hua; Lu, Mei-Chun; Hsieh, Ling-Yu; Lin, Tzu-Chia
Most children experience significant anxiety during the preoperative period. Greater preoperative anxiety may be related to a higher incidence of negative behaviors. This study aimed to develop a family-centered preoperative preparation program and to evaluate the effects of this program on children's preoperative emotional behaviors, postoperative behavior, and posthospital behavior, and on caregiver anxiety. A prospective, randomized controlled study was conducted. The population consisted of children who underwent minor surgery and their caregivers. The control group received standard care, and the experimental group received standard care plus preoperative preparation, which included a tour, a cartoon video depicting a boy's surgical journey, and familiarization with medical equipment. Children's emotional behaviors and caregiver anxiety were measured at the preoperative visit, in the preoperative holding area, and at induction of anesthesia. Postoperative behavior was measured when children were in the recovery room, and the researcher also contacted caregivers 2 weeks after the surgery to assess the children's behavior at home. A linear mixed-effects model results showed that as the surgery approached, the experimental group had fewer and more stable preoperative emotional behaviors (least squares means of preoperative emotional behaviors from preoperative visit to induction of anesthesia = 10.01-10.95). However, the control group exhibited significantly increased preoperative emotional behaviors as the surgery approached (least squares means of preoperative emotional behaviors from the preoperative visit to induction of anesthesia = 7.87-12.23). Family-centered preoperative preparation can effectively improve children's negative emotional behaviors from their time in the preoperative holding area to the induction of anesthesia.